Trade Union Advisory Medical Officers - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
1920 1920 1920s 9 pages acquire more weight in Hospital and medical counsels of the country, and to attempt to obtain for individual Trade Unionists a system which would minimise the chances of his obtaining superficial or inadequate treatment. Many Trade Unionists come under the National Insurance Acts and are scattered among the different panel doctors of the country. In some districts, the panel system is not working satisfactorily as far as the treatment of patients is concerned. No medical system will eliminate the groumbler [grumbler] and the dissatisfied, but what has the powerful Trade Union movement as a whole done in the way of investigation or suggestion of improvement in the panel system of the country for its members? A few remarks are made on this subject in the first memorandum. Many private firms are considering the question of a more efficient medical service for its employees. And the quotation from the Daily Herald of June 30th given below will demonstrate the nature of the schemes suggested. As one who has been giving this particular question much thought in recent years, it is modestly suggested that individual Trade Unions should either prepare schemes suitable for their Unions, or should ask that schemes suitable to them may be submitted for consideration, and further that, before the medical service schemes or private employers become moulded into vested interests, the Trade Union movement should take up this idea and have schemes of their own ready as soon as possible. The status of the Advisory Medical Officer alone ought to secure reduction in specialists' fees, and more speedy admission to institutions for individual Trade Unionists. Cutting from DAILY NEWS, Wednesday, June 30th, 1920. MEDICAL AID FOR NEW POOR. Specialists and Nursing Homes at Reduced Fees. "First-rate medical advice for the new poor whose incomes ''have not advanced by 200% or 300% since 1914" is provided for in a scheme developed by the firm of Thomas de la Rue and Co. Ltd. The first step in the preparation of the scheme was to extend the medical service of the company so as to include an organisation of eminent consulting physicians and surgeons who would agree to treat privately patients sent by the company at fees reduced in such a way that individuals should pay only according to their ability. A definite scale of charges is laid down. Thus a man with an income of under £350 pays only 10% of operation fees, and 25% of consultation, treatment or nursing home fees. When the income rises to £1,500, the proportions are 60% for operations and full fees for consultations. Further plans are now in hand for the establishment of a large nursing home, where patients can be received at low fees payable according to their means. To provide the necessary funds, it is proposed to issue 7½% debentures. A sinking fund of 5% per annum will be provided, and any surplus profit is to be devoted to improving the service, and further reducing the charges. The names of those who have consented to become consultants to the Company include most of the best-known Harley Street and Wimpole Street names. A distinguished physician says; ''If a similar scheme became more general, we should have solved one of the greatest of the many social problems that face us." Other large employers are being approached, with a view to inviting them to subscribe substantial sums towards the erection of the proposed nursing home." 36/H24/11